Analysis of Spatial Layout Design and Its Impact on Circulation Comfort at the Homedec Exhibition in ICE BSD Jakarta - Ni Made Suci Arini; Ngurah Gede Dwi Mahadipta; I Putu Gede Suyoga (Gorga : Jurnal Seni Rupa, 2025)
This research aims to analyze the implementation of spatial layout in relation to visitor circulation comfort at the HOMEDEC 2024 Exhibition, held in Hall 3A of the Indonesia Convention Exhibition (ICE) BSD, Jakarta, from October 3rd to 6th, 2024. The background of this study is rooted in the importance of spatial arrangement to support smooth visitor flow and enhance the overall visitor experience during large-scale exhibition events. This study employs a descriptive qualitative research method, using data collection techniques such as direct observation, expert interviews, documentation, and the distribution of questionnaires to exhibition visitors. The analysis focuses on aspects including circulation path width, movement patterns, booth placement, zoning, and wayfinding within the exhibition space. The findings indicate that the spatial layout, designed using a combination of grid and radial patterns, successfully facilitated a relatively smooth flow of movement. However, several congestion points were identified, particularly in the prize giveaway area, the main stage area, and at the intersections of major circulation paths. Supporting factors that contributed to visitor comfort at the HOMEDEC exhibition included adequate main path widths, good lighting, and strategic booth placement. Nevertheless, limited boundary signage and high density in certain zones emerged as key constraints. This study recommends improvements in zone organization, widening of pathways in high-traffic areas, and the addition of directional signage to further enhance visitor circulation comfort in future exhibitions.